Trudne pytanie o tożsamość informatyki. O podstawowych sposobach rozumienia terminu informatyka - Szynkiewicz, Mariusz (Człowiek i Społeczeństwo, 2025)
The text is methodological in nature and raises definitional issues related to the development of the concept of computer science. Based on studies in the history of computing, computer science, philosophy of technology and science methodology. The author analyzes the basic ways of understanding term computer sciences. The article indicates three definitional (scope) approaches that dominate scientific considerations. The author also indicates the main methodological problems related to the functioning of the concept of computer science in contemporary science and technology and possible ways to solve this issues.